Surdez, linguagem e conhecimento na educação superior : trajetórias formativas de surdos no Brasil e no México - Bazilatto, Alexandre (2017)
This study aims to analyze notions of deafness, language and knowledge underlying the formative-educational processes of deaf students in Higher Education in a Brazilian and Mexican realities in order to a) know the formative processes of two deaf students in a university context being one Mexican (Veracruzana University – UV) and one Brazilian (State of Espirito Santo Federal University – UFES); b) understand the conceptions and expectations of these deaf students regarding their formative trajectory in Higher Education; c) know aspects of the formative experiences lived by these deaf students in different contexts, especially, in Higher Education. It is a research of qualitative nature anchored in the field of case studies (ANDRÉ, 2005). In theoretical-methodological terms we have taken on an investigative perspective encompassing the Compared Education as an interdisciplinary field based on a dynamic and methodologically open knowledge (SOBRINHO et al. 2015) sustained by Figurational Sociology assumptions prepared by Norbert Elias, especially the concepts of language and knowledge (ELIAS, 1994b), figuration and interdependence (ELIAS, 1994a; 2001a; 2014) in dialogue with the literature about educational policies and with authors who discuss the education of the deaf. Therefore, our reflections take on a historical-sociological approach of the educational phenomenon. We collected data through the study of documents and the analysis of Brazilian and Mexican educational census, but we focused on the narratives collected through interviews with two deaf students. The first enrolled at the State of Espirito Santo Federal University – Brazil and the second enrolled at the Veracruzana University – Mexico. We observed that in these two countries the education of the deaf follows the purposes of international agreements which aim at broadening the access to Higher Education endorsing an education for all. In this process, the linguistic specificity of the deaf is repeatedly neglected influencing the concretization of the announced policy. We highlight that notions of deafness, language and knowledge are frequently outlined in the formative process under a listening-centered logic leading to educational implications especially in reference to methodological strategies and the interrelations established in the Higher Education in these two countries. On the other hand, we observed that cooperation attitudes between the nondeaf (family members, friends, classmates, and others) and the deaf broaden the interdependence network contributing to the re-signification of language concepts, knowledge and deafness collaborating in the formative-educational process of the deaf students in university contexts in Brazil and Mexico.